Representasi Persahabatan pada Anime “Bocchi The Rock!” - Annisa Cahya Maulani; Arif Surya Kusuma (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Friendship can be defined as a relationship with deeper emotional closenes by establishing a connection through greater openness and strengthened togetherness. The relationship of friendship is a close bond that is often used as a theme in various forms, such as films, novels, and television series. The form of friendship can be observed through a Japanese television series, the anime Bocchi The Rock!. The purpose of this study on friendship is to understand how friendship is represented in the anime Bocchi The Rock!. The qualitative method was used as the approach in this study. This research also used Roland Barthes semiotic analysis by examming denotation, connotation, and myth meanings as reflected through visualizations of atmosphere, expressions, and dialogues. By using this analysis, it was shown that the friendship represented in Bocchi The Rock! revealed three important aspects of friendship. These three important aspects of friendship. These three aspects were: understanding personality differences through friendship relationships, fulfilling affectional needs through friendship relationships, fulfilling affectional needs through friendship bonds, and enhancing the quality of friendship by providing emotional support.